Hard Skill and Soft Skill Training Through Outbound Game for Children in TPQ Nurul Qoryah Mulur Sukoharjo - Tira Nur Fitria (Universitas Negeri Padang Press, Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi, Fakultas Ilmu Keolahragaan, Univeristas Negeri Padang., 2022)
This community service activity aims to train soft skills and hard skills through outbound games for the children in TPQ Nurul Qoryah Mulur Bendosari Sukoharjo. This community service activity uses the simulation/demonstration method. This activity is implemented on Sunday, 5 June 2022 at 06.00 - 09.00 WIB at the field. The number of students in this outbound is 20 which are divided into 4 or 5 groups. With the average age of four to eight years of TPQ students, the division of groups is carried out very carefully, so that the group is divided fairly and the game is fun. This outbound started at 08.00 - 11.00 WIB. In outbound games, lecturers in community service activities teach playing raffia rope circles. This activity can practice solving abilities, practice patience, mutual understanding, accuracy, speed, and cohesiveness in rope games. We only need to prepare the raffia rope to play this game. Then, we just need to make a circle with the rope. When signaled, all players on the team must enter the circle that has been created. If no participant enters then all participants will be penalized. The players also need to instill an attitude of mutual trust between participants in teammates to play a circle of ropes. With this trust, participants are expected to be able to establish better relationships and be able to help each other in any way. Although this game is very simple, the students look very happy when they follow the game, they can also learn to work together and train cohesiveness in a team. The outbound has received a positive response from participants. This is illustrated by the high enthusiasm of TPQ Nurul Qoryah's children in participating in this outbound activity.